Determination of the force transmitted by an ion thruster plasma plume to an orbital object. (February 2016) - Alpatov, A.; Cichocki, F.; Fokov, A.; Khoroshylov, S.; Merino, M.; Zakrzhevskii, A.
Abstract: An approach to determine the force transmitted by the plasma plume of an ion thruster to an orbital object immersed in it using its central projection on a selected plane is proposed. A photo camera is used to obtain the image of the object central projection. The algorithms for the calculation of the transmission of momentum by the impacting ion beam are developed including the determination of the object contour and the correction of the error due to a camera offset from the ion beam axis, and the computation of the fraction of the ion beam that impinges on the object surface. Highlights: New approach to determine the force transmitted by an ion beam to a downstream target. Intended for contactless active space debris removal with an ion beam shepherd. The contour of the conic projection of the target is the only required information. Investigates inaccuracies when the conic projection is obtained with an offset camera. Numerical calculations illustrating the proposed approach are presented.